The Development of Vocabulary Learning Media By Using "Mini Walking Dictionary" Refers to the Project-Based Learning to the Students of Vocational High School - Atinia Hidayah (CLLiENT (Culture, Literature, Linguistics, and English Teaching), 2019)
The ability of a person to speak English as a mean of communication both oral and written is influenced by mastering the vocabulary. Unfortunately, the vocabulary lessons are considered as old learning and it's abandoned by English teachers today. “Mini Walking Dictionary” offers the solution. This dictionary is developed from students' project-based learning and enhanced through 4 stages: the define phase, the design phase, the development phase and the disseminate phase. Thus it will create a valid and practical vocabulary media for students. Mini Walking Dictionary has been arranged based on the students' condition and characteristic aspects that all of them have been analyzed in detail. Therefore, Mini Walking Dictionary is very appropriately used to help the English teachers as a first step in overcoming the problems of students who have difficulty in learning English both oral and written. Keywords: Learning media, the development of learning media, Mini Walking Dictionary, Vocabulary learning, project-based learning.